2020
DOI: 10.3390/jcm9051411
|View full text |Cite
|
Sign up to set email alerts
|

Macular Ganglion Cell Layer Thickness after Macula-Off Rhegmatogenous Retinal Detachment Repair: Scleral Buckling versus Pars Plana Vitrectomy

Abstract: (1) Background: We evaluated macular ganglion cell layer–inner plexiform layer (GCL-IPL) thickness in patients with primary macula-off rhegmatogenous retinal detachment (RRD) treated with scleral buckling (SB) or pars plana vitrectomy (PPV) using spectral domain optical coherence tomography (SD-OCT). (2) Methods: In this retrospective, observational study, we reviewed the medical records of patients undergoing SB or PPV surgery for macula-off RRD. SD-OCT was performed at three and 12 months after surgery. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…As part of a standardized protocol, the circumference of the 240 encircling band was shortened by 10 mm and transscleral cryotherapy was performed to the retinal break(s). A 287 circumferential silicone scleral explant was finally positioned to support the break(s) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…As part of a standardized protocol, the circumference of the 240 encircling band was shortened by 10 mm and transscleral cryotherapy was performed to the retinal break(s). A 287 circumferential silicone scleral explant was finally positioned to support the break(s) [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…412 Coppola et al reported that the main structural cross-sectional OCT findings after vitreoretinal surgery for RRD included subretinal fluid, subretinal blebs, retinal folds, subretinal perfluorocarbon liquids, macular alterations related to silicone oil, epiretinal membranes, proliferative vitreoretinopathy, cystoid macular edema, macular holes, and recurrent retinal detachment. 13 Additionally, thinning of macular ganglion cell-inner plexiform layer has been observed in patients with RRD treated with PPV, 14 while thickening of peripapillary retinal nerve fiber layer in successfully operated RRD eyes using vitrectomy and silicone oil endotamponade has been also reported. 15…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, a retrospective cohort of 822 patients, the PPV group had a higher average proportion of surgical failures than the SB group [14]. In eyes with macula-off RRD treated with PPV, the macular ganglion cell layer-inner plexiform layer (GCL-IPL) was found to be significantly thinner compared to eyes undergoing scleral buckling surgery [15]. Furthermore, Znaor reported in a cocharne review of 10 Randomized controlled trials of 1307 eyes, found no difference between PPV and scleral buckling in terms of operation success and vision achieved and PPV can be linked to a lower risk of detachment recurrence.…”
Section: Discussionmentioning
confidence: 91%